Pengaruh temperatur kalsinasi terhadap struktur tembaga oksida dari daerah Pinti Kayu Kecamatan Koto Parik Gadang Diateh Kabupaten Solok Selatan (The effect of calcination temperature on the copper oxide structure of the Pinti Kayu area, Koto Parik Gadang Diateh District, South Solok Regency) - Robby Zeffry; - Ratnawulan; - Yohandri (Department of Physics – Universitas Negeri Padang UNP, 2015)
The purpose of this study was to determine the levels of copper oxide content and analyze the effect of calcination temperature on the physical properties of copper oxide from Pinti kayu areas, district Koto Parik Gadang Diateh regency of Solok Selatan. This analysis is important to identify the quality of the copper ore. The characterization using X-ray Fluorescence (XRF) and X-Ray Diffraction (XRD). Based on measurement result (CuO) the percetage of coper oide is about 89.65%. The results of XRD analysis shows due to the influence of calcination temperature at a temperature of 145°C copper oxide structure changes from monoclinic to hexagonal structure at a temperature of 300°C, then at a temperature of 850°C into a cubic structure and at a temperature of 1000°C copper oxide into monoclinic structure